What should a dictionary contain to be useful for translators? - Buendía-Castro, Míriam (Lexicography, 2024)
Translators are one of the main groups of dictionary users. The design, revision, and compilation of any kind of lexicographic or terminographic resource for translators should thus be based on their specific needs. To this end, the research examined the importance attributed by 221 BA and MA trainee translators to the various types of information in a dictionary entry, with a view to determining which are most useful for translation. Also identified were the differences between an ideal entry for translators and one for the general public. The results showed that the students' answers varied depending on their year of study, as well as whether they were on the BA or MA program. The data collection tool was a self-reported questionnaire. The dictionary information most valued by trainee translators was usage contexts, definitions, phraseology, and translation equivalents. Furthermore, students at higher academic levels attributed more importance to usage contexts and phraseology. This study highlights the need to include phraseological and contextual information in the entries of translation-oriented dictionaries.